THE ANALYSIS OF STUDENTS’ NEED IN LEARNING ENGLISH (A DESCRIPTIVE QUALITATIVE RESEARCH DESIGN TOWARD STUDENTS OF LAW AND BUSINESS ADMINISTRATION UNIVERSITY OF KAPUAS SINTANG) - Agustinus Marjun (Universitas Kapuas, 2022)
This study is intended to analyze students’ need in learning English for specific purposes. This descriptive qualitative research design is engaged 50 students as participants. There are 25 of Law students and 25 of business students are chosen as participants of this study. This study is provided 9 items of questionnaire as the tool for data collecting. SPSS as the medium for helping the researcher in analyzing data collection. The result of this study revealed that the most difficulties aspect in learning English is aspect of speaking. Meanwhile, the main purpose of students to learn English is to be able to speak English fluently. This result as important feedback for the instructors or lecturer to decide what should be done in providing an appropriate material in English class based on students’ needs.